2005
DOI: 10.1259/dmfr/57066369
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of schwannoma with marked cystic changes

Abstract: We report two cases of schwannoma displaying marked cystic changes; one in the temporalis muscle and one in the submandibular space. The first patient, a 44-year-old male, presented after complaining of a swelling rapidly increasing in size in the left temporal region. Computed tomography (CT) indicated a low-density area surrounded by soft tissue. Magnetic resonance imaging (MRI) revealed signal hypointensity on T1 weighted imaging and strong signal hyperintensity on T2 weighted imaging. The extirpated tumour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…FNAC in schwannomas may be inconclusive due to haemarhagic aspirate or inadequate cellular materials. 4 In our case FNAC was suggestive of brachial cleft cyst.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…FNAC in schwannomas may be inconclusive due to haemarhagic aspirate or inadequate cellular materials. 4 In our case FNAC was suggestive of brachial cleft cyst.…”
Section: Discussionsupporting
confidence: 48%
“…It shows low intensity flow void giving characterstic "salt and pepper" appearance and has delayed wash out time on diffusion weighted imaging. 4 CT scans show a homogenous regular hypodense swelling which slightly enhance on contrast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of ECT mimicked metastatic lymph nodes, but no primary tumour was detected by the systemic imaging survey (Figure 2a). Schwannomas with cystic changes have been reported previously, 13,14 so radiologists should consider schwannoma based on their knowledge of the anatomy and the physical characteristics of nearby nerves when a well-defined, circular-type mass with an enhanced wall and cystic components with no invasion of the mass into the adjacent tissues is found by imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Wakoh et al 34 reported two cases of schwannoma displaying marked cystic changes; one in the temporalis muscle and one in the submandibular space. They concluded that MRI should depict the nerves and allow identification of the origin of a schwannoma.…”
Section: Discussionmentioning
confidence: 99%